A Teaching Model for Developing Public Speaking Competence - Tomaž Petek (Jezikoslovni zapiski)
This article presents a teaching model for developing public speaking competence that also offers every public speaker later critical monitoring of his own progress and awareness of this area. Namely, effective public speaking is something that needs to be learned. The teaching model presented is composed of criteria for assessing speaking in public and recommendations based on them for successful and effective public speaking. Mastering this area is a precondition for every individual’s personal and professional success.